2010
DOI: 10.1007/s12011-010-8839-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Forms of Dietary Selenium Supplementation on Growth Performance, Meat Quality, Selenium Deposition, and Antioxidant Property in Broilers

Abstract: This study was conducted to investigate the effects of different sources of dietary selenium (Se) supplementation on growth performance, meat quality, Se deposition, and antioxidant property in broilers. A total of 600 one-day-old Ross 308 broilers with an average body weight (BW) of 44.30 ± 0.49 g were randomly allotted to three treatments, each of which included five replicates of 40 birds. These three groups received the same basal diet containing 0.04 mg Se/kg, supplemented with 0.15 mg Se/kg from sodium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 44 publications
(41 reference statements)
9
51
3
Order By: Relevance
“…Chen et al, (2014) noted significantly higher liver GPx activity in selenium yeast supplemented group than that sodium selenite supplemented group, while Wang et al, (2011), in line with current study, observed similar activity in these two groups. In contrary, Edens, (2002) reported a steady state release of selenium from organic selenium for incorporation into the glutathione peroxidase antioxidant system which resulted in increased GPx activity.…”
Section: Antioxidant Status Of Birdssupporting
confidence: 89%
See 1 more Smart Citation
“…Chen et al, (2014) noted significantly higher liver GPx activity in selenium yeast supplemented group than that sodium selenite supplemented group, while Wang et al, (2011), in line with current study, observed similar activity in these two groups. In contrary, Edens, (2002) reported a steady state release of selenium from organic selenium for incorporation into the glutathione peroxidase antioxidant system which resulted in increased GPx activity.…”
Section: Antioxidant Status Of Birdssupporting
confidence: 89%
“…But enzyme activity was similar between inorganic and organic selenium supplemented groups which were in line with the current study. Earlier studies by Wang et al, (2011), Ozkan et al, (2007, Jiang et al, (2009), Zoidis et al, (2010), Upton et al, (2009), Chen et al, (2013, Rajashree et al, (2014), Edens and Sefton (2016), Gogmen et al, (2016) and Bakhshalinejad et al, (2018) observed increased glutathione peroxidase activity in various tissues of broiler such as liver, breast muscle, blood and serum as influenced by supplementation of organic sources of selenium.…”
Section: Antioxidant Status Of Birdsmentioning
confidence: 91%
“…For example, in a study examining different Se sources, activity of GPx in the liver was greater in hens fed selenite or Se yeast but was higher in plasma in hens fed selenite compared with B-Traxim Se or Se yeast (Leeson et al, 2008). In contrast, no differences were detected with respect to GPx activities in the serum and tissues between the sodium selenite and the L-SeMet groups (Wang et al, 2011b). It therefore seems that many factors may be involved in tissue Se retention and GPx activity.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding nano-materials, nano-Se has been reported to exhibit high-specific surface area, small particle size and good intestinal absorption because of the formation of nanoemulsion droplets (Hu et al, 2012). Similarity between SeMet and Met allows the body to use them interchangeably in protein synthesis because the tRNAMet cannot discriminate between Met and SeMet (Wang et al, 2011b). This makes it possible to build Se reserves in the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation